The green biorefinery concept for the valorisation of pistachio shell by high-pressure CO2/H2O system - Özbek, Hatice Neval (2019)
ABSTRACT: The use of high-pressure CO2/H2O in valorisation of pistachio shell to produce hemicellulose-derived, oligomeric and monomeric sugars and their further transformation to furfural as well as enzymatic transformation of cellulose-rich solids is presented in this work. Different pre-treatment conditions i.e. temperature ranged from 160 to 200 degrees C; reaction time varied between 0 and 30 min and liquid to solid mass ratio between 4 and 8 with constant initial pressure of CO2 of 50 bars were examined. At the optimal pre-treatment conditions, the concentrations of xylose and xylo-oligosaccharide were of 1.7 and 35.5 g/L. Furthermore, this work demonstrates the high-pressure CO2 catalysed production of furfural in an aqueous/tetrahydrofuran system. For model solution containing a mixture of xylose and acetic acid, the optimised furfural yield was as high as 53.3 mol%, while for real sample of hemicellulose hydrolysate, the furfural yield of 39.6 mol% and the selectivity of 40.0 mol% were obtained. Additionally, quantitative glucan to glucose conversion by enzymatic hydrolysis of pre-treated cellulose-rich biomasses was achieved.